Efeito do tempo entre passes na interação recristalização-precipitação de um aço inoxidável austenítico com alto teor de nióbio e nitrogênio - Silva, Mariana Beatriz dos Reis (Universidade Federal de São Carlos, 2014)
In this work was studied the influence of interpass time on the recrystallizationprecipitation interaction occurring during the thermomechanical processing of ISO 5832-9 austenitic stainless steel, which has high contents of niobium (0.28%) and nitrogen (0.35%). The simulation of the industrial processing was carried out through hot torsion testing with multiple deformations in continuous cooling, in which the interpass time ranged between 5 and 50 s. The obtained plastic flow curves showed that shortest interpass times lead to increased levels of stress during straining and that the non-recrystallization temperature for this steel is close to 1100°C. The microstructural evolution was investigated by interrupting the tests on certain deformations before and after Tnr, and for this it was used the microscopy techniques of optical, transmission electron and scanning electron associated with electron backscattered diffraction. Small interpass times resulted in a larger volume fraction of small precipitates (< 50 nm) and smaller grain sizes. It was observed that dynamic recrystallization also occurs, and that these smaller precipitates were effective in pinning grain boundaries and dislocations (continue...).
Effect of interpass time on recrystallization-precipitation interaction of high niobium and nitrogen austenitic stainless steel
Keywords: Metalurgia física; Recristalização e precipitação; Refino de grão; Nióbio; Processamento termomecânico; Aço inoxidável; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA